2020
DOI: 10.1055/s-0040-1714750
|View full text |Cite
|
Sign up to set email alerts
|

Radial Shortening Osteotomy for Symptomatic Kienböck's Disease: Complications and Long-Term Patient-Reported Outcome

Abstract: Objective To determine the rate of salvage procedures and any other unplanned reoperations in patients with symptomatic Kienböck's disease who were treated with radial shortening osteotomy. In addition, we studied patient-reported outcome in the long term using Patient-Reported Outcome Measure Information System (PROMIS) instruments. Methods We performed a retrospective review of all patients who underwent radial shortening osteotomy for stage 2 and 3A Kienböck's disease. Patients who had concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Two studies reported a mean of 2 mm of RS, with ranges of 1–5 mm and 1.5–2.5 mm. 7 , 8 One study reported a mean of 3 mm, with a range of 1–4 mm. 9 Four studies reported an RS of 2–3 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported a mean of 2 mm of RS, with ranges of 1–5 mm and 1.5–2.5 mm. 7 , 8 One study reported a mean of 3 mm, with a range of 1–4 mm. 9 Four studies reported an RS of 2–3 mm.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported that radial shortening provides acceptable clinical results for Kienböck’s disease 27 29 , and that this osteotomy achieves revascularization and unloads the diseased lunate 10 , 30 , 31 . Several biomechanical studies have demonstrated that radial shortening unloads the lunate by shifting the load toward the distal ulna 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that radial shortening provides acceptable clinical results for Kienböck disease, [11][12][13] and that this osteotomy achieves revascularization and unloads the diseased lunate. [14][15][16] Several biomechanical studies have demonstrated that radial shortening unloads the lunate by shifting the load toward the distal ulna.…”
Section: Discussionmentioning
confidence: 99%